Learning My Way: A Pilot Study of Navigation Skills in Cerebral Palsy in Immersive Virtual Reality - Biffi, Emilia; Gagliardi, Chiara; Maghini, Cristina; Genova, Chiara; Panzeri, Daniele; Redaelli, Davide Felice; Turconi, Anna Carla (Frontiers in Psychology, 2020)
Purpose: Human navigation skills are essential for everyday life and rely on several cognitive abilities, among which visual-spatial competences that are impaired in subjects with Cerebral Palsy (CP). In this work, we proposed navigation tasks in Immersive Virtual Reality (IVR) to 15 children with CP and 13 typically developing (TD) peers in order to assess the individual navigation strategies and their modifiability in a situation resembling real life. Methods: We developed and adapted to IVR an application based on a 5-way maze in a playground that was to be navigated to find a reward. The learning process, navigation strategies and adaptation to changes were compared between participants with CP and their TD peers and correlated with visual-spatial abilities and cognitive competences. Results: Most participants with CP needed more attempts than TD participants to become proficient in navigation. Furthermore, the learning phase was correlated to visual-spatial memory but not with cognitive competences. Interestingly, navigation skills were comparable between groups after stabilization. While TD participants mainly relied on allocentric strategies based on environmental cues, egocentric (self-centred) strategies based on body motion prevailed in participants with CP. Furthermore, participants with CP had more difficulties in modifying their navigation strategies, caused by difficulties in executive processes beyond the visual-perceptual impairment, with an inefficient shift between implicit and explicit competences. Conclusions: The navigation abilities in participants with CP seem to be different from their TD peers in terms of learning and adaptation to new conditions; this could deeply affect their everyday life and ultimately participation and inclusion. A regular assessing and focused rehabilitative plans could help to better navigate the environment and affect self-perception.